NEGLECTING WOMEN'S RIGHTS: Indonesian YouTube Preachers' Legal Opinion on Polygamy - Yazid, Mhd (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2023)
The internet has contributed to the rise of various authorities over religion and law, as a result of the widespread use of digital instruments by religious elites to transmit their knowledge of virtue. Therefore, religious-based legal opinions are easily disseminated through social media. This article discusses video content related to polygamy that is delivered by preachers on YouTube channels. The discussion revolves around the legal aspects of polygamy described by the YouTube preachers to see the extent to which the polygamous content provides an understanding to the Indonesian public about polygamy law and its relation to the protection of women's rights. Data was collected through content analysis of either monologue or dialogue from popular preachers. This article argues that classical fiqh narratives of polygamy remain the tenet of the content about the polygamy landscape on YouTube. It does not significantly represent Indonesia's marriage law and arguably has not provided progressive protection for women’s rights. Most of the principles and arguments used lead to the nobility of polygamy, women's patience, maintaining the integrity of the household, and prohibiting breaking the Sharia.[Internet telah berkontribusi pada munculnya berbagai otoritas atas agama dan hukum, sebagai akibat dari maraknya penggunaan instrumen digital oleh para elit agama untuk mentransmisikan pengetahuan mereka tentang kebajikan. Oleh karena itu, opini hukum berbasis agama mudah disebarluaskan melalui media sosial. Artikel ini membahas tentang konten video terkait poligami yang dibawakan oleh para da'i di kanal YouTube. Pembahasan mencakup aspek hukum poligami yang dipaparkan oleh para da'i YouTube untuk melihat sejauh mana konten poligami memberikan pemahaman kepada masyarakat Indonesia tentang hukum poligami dan kaitannya dengan perlindungan hak-hak perempuan. Data dikumpulkan melalui analisis isi baik monolog maupun dialog dari da’i populer. Artikel ini berpendapat bahwa narasi fikih klasik tentang poligami tetap menjadi inti konten tentang poligami di YouTube. Itu sama sekali tidak merepresentasikan hukum perkawinan menurut negara dan bisa disimpulkan belum memberikan perlindungan yang progresif bagi hak-hak perempuan. Sebagian besar prinsip dan dalil yang digunakan antara lain kesabaran perempuan, menjaga keutuhan rumah tangga, dan melarang melanggar syariat—yang pada akhirnya, semua opini itu diarahkan untuk meluhurkan poligami itu sendiri.]